Biomarkers in systemic sclerosis. Issue 6 (November 2019) - Skaug, Brian; Assassi, Shervin
Abstract : Purpose of review: To discuss recent advances in identification of biomarkers in systemic sclerosis for disease severity, prognosis, and treatment response. Recent findings: Recent reports describe novel circulating markers of disease severity, autoantibody associations with specific manifestations including cancer, and skin gene expression-based predictors of modified Rodnan skin score progression and treatment response. Moreover, there is converging evidence that C-reactive protein and pneumoproteins such as Krebs von den Lungen-6 and chemokine ligand 18 could serve as prognostic biomarkers in systemic sclerosis-associated interstitial lung disease. Summary: Several novel biomarkers show promise in improving the assessment of systemic sclerosis (SSc) disease severity, prognosis, and treatment response. Their potential utility in prospective selection of patients for clinical trials and in individual patient management require additional research.